A Disulfide Bond in the Membrane Protein IgaA Is Essential for Repression of the RcsCDB System - Pucciarelli, M. Graciela; Rodríguez, Leticia; García-del Portillo, Francisco (Frontiers in Microbiology, 2017)
IgaA is an integral inner membrane protein that was discovered as repressor of the RcsCDB phosphorelay system in the intracellular pathogen Salmonella enterica serovar Typhimurium. The RcsCDB system, conserved in many members of the family Enterobacteriaceae, regulates expression of varied processes including motility, biofilm formation, virulence and response to envelope stress. IgaA is an essential protein to which, in response to envelope perturbation, the outer membrane lipoprotein RcsF has been proposed to bind in order to activate the RcsCDB phosphorelay. Envelope stress has also been reported to be sensed by a surface exposed domain of RcsF. These observations support a tight control of the RcsCDB system by RcsF and IgaA via mechanisms that, however, remain unknown. Interestingly, RcsF and IgaA have four conserved cysteine residues in loops exposed to the periplasmic space. Two non-consecutive disulfide bonds were shown to be required for RcsF function. Here, we report mutagenesis studies supporting the presence of one disulfide bond (C404 C425) in the major periplasmic loop of IgaA that is essential for repression of the RcsCDB phosphorelay. Our data therefore suggest that the redox state of the periplasm may be critical for the control of the RcsCDB system by its two upstream regulators, RcsF and IgaA.